The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1016/j.bbrc.2007.05.182
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/CXCL12 axis promotes VEGF-mediated tumor angiogenesis through Akt signaling pathway

Abstract: CXC chemokine receptor 4 (CXCR4) has been shown to play a critical role in chemotaxis and homing, which are key steps in cancer metastasis. There is also increasing evidence that links this receptor to angiogenesis; however, its molecular basis remains elusive. Vascular endothelial growth factor (VEGF), one of the major angiogenic factors, promotes the formation of leaky tumor vasculatures that are the hallmarks of tumor progression. Here, we investigated whether CXCR4 induces the expression of VEGF through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
218
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(235 citation statements)
references
References 25 publications
9
218
0
Order By: Relevance
“…While, Kijowski et al 35 demonstrated the stimulation of VEGF secretion by SDF-1-CXCR4 axis, using human hematopoietic cell lines. Because then, a close correlation between CXCR4 and VEGF expression has been demonstrated in epithelial malignancies 12,13 and osteosarcoma, 36 both in vitro and in vivo. In our previous study, we found a significant positive correlation between immunohistochemical VEGF and CXCR4 expression.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While, Kijowski et al 35 demonstrated the stimulation of VEGF secretion by SDF-1-CXCR4 axis, using human hematopoietic cell lines. Because then, a close correlation between CXCR4 and VEGF expression has been demonstrated in epithelial malignancies 12,13 and osteosarcoma, 36 both in vitro and in vivo. In our previous study, we found a significant positive correlation between immunohistochemical VEGF and CXCR4 expression.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9] Some investigators have revealed that exogenous VEGF up-regulated CXCR4 expression in human endothelial cells. 10,11 A close correlation between CXCR4 and VEGF expression has been demonstrated in a breast cancer cell line through the PI3K/Akt pathway, 12 and in pancreatic cancer cell lines through ERK pathway. 13 Moreover, a strong relationship between CXCR4 and VEGF mRNA levels has been demonstrated in breast cancer tumor tissue.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Given the general crucial role of PKB in cell motility [23], it is not surprising to observe a key contribution of PKB in lymphocyte chemotactic migration. Indeed, activation of PKB is induced by S1P (ligand for S1P1) [34], CCL19/CCL21 (ligands for CCR7) [34], CXCL13 (ligand for CXCR5) [34] and CXCL12 (ligand for CXCR4) [35], most probably downstream of PI3 K [34]. Interestingly, PKB dependent phosphorylation of S1P1 is required for S1P1 mediated chemotaxis [36].…”
Section: Immune Cell Intrinsic Role Of Pkb In Motility Activation Dmentioning
confidence: 99%
“…Moreover, PKB activation induced by PTEN loss promotes prostate tumor growth and metastasis by up-regulating CXCR4 expression [78]. CXCR4 activation can further boost PKB activity [35,79]. Functionally, PKB activation is required for CXCR4-induced cancer cell migration [80].…”
Section: Role Of Tumor-derived Pkb Activity In Inflammationmentioning
confidence: 99%